Allgarve events: Implications for the Algarve image - Manuela Guerreiro, Maria (2014)
Located in the south of Portugal, the Algarve belongs to the top twenty travel destinations worldwide, with a local economy relying strongly on tourism-related activities. The Allgarve programme was launched in 2007 and is an umbrella brand that aims to reposition the Algarve as a refi ned tourism destination with glamour. Allgarve is a set of cultural, artistic and sports events off ered mainly during the summer season. Based on data from a questionnaire carried out with 282 foreign tourists who visited the Algarve, this study identifi es and profi les clusters of tourists based on their perceptions of Allgarve. In addition, we analyse to what extent the image of the Algarve has changed as a consequence of the Allgarve events. The results show that most respondents agree with the Allgarve brand name, report a positive perception of the campaign, and agree that it has a positive impact for the Algarve differentiation. However, the results suggest that the majority of tourists still come to the region attracted by the Algarve brand, and that this brand has not been aff ected by the Allgarve programme's content. Th e fi ndings of this study are important in understanding the implications of events in repositioning strategies of mature tourism destinations.